Not reading: the new forms of censorship in the bibliographic and publishing circuit - Cordón-García, José-Antonio; Muñoz-Rico, María (Anuario ThinkEPI, 2023)
Censorship is a phenomenon that has been present in the history of reading and publishing since books began to consolidate as the preferred format for the transmission of thought. Powers of all kinds, both civil and ecclesiastical, combated any form of deviation or dissent from official doctrines through the prohibition of works and the persecution of authors, printers, booksellers, and publishers. With several centuries of validity, its exercise was an insurmountable and pernicious obstacle in the process of transferring any type of information. When it had seemed to have disappeared thanks to the generalization of human rights, mainly those related to freedom of expression, it has now returned in our days with special virulence in the form of revisions of classic literature according to the patterns of political correctness under the purging, elimination, or prohibition of works in public and school libraries in response to the demands of conservative or extreme right-wing pressure groups. We are at a time when these new forms of censorship, open in some cases and subliminal and subtle in others, threaten to hinder not only the freedom of access to information, but also the cultural memory of the places where they are exercised.